Digital Project Management as A New Work Environment Innovation Post-Pandemic - Ibnu Kholdun, Amrulloh; Olivia Bistolen, Fanesia (Siber Journal of Transportation and Logistics, 2024)
Organizations engage in projects that bring about change, such as the creation of new goods and services or the improvement of business processes to achieve value. According to Williamson and Wu (2019), projects are “time-limited, goal-driven, and often unique endeavors intended to create an outcome, service, product, or final result.” These projects can include improving existing products and creating new services, improving an organization through a transformation process, launching a new marketing campaign to increase market penetration, organizing an event such as a conference or sports match, and Projects have several challenges that make them more difficult than many management ventures, such as scope of work, time, resources, and budget.